SME Center Development Strategy Langkat Furniture in an Effort to Increase Competitiveness with SWOT Analysis and QSPM - Abdul Jaminson; Aulia Ishak; Anizar (TALENTA Publisher, 2025)
The construction of an SME center is an alternative for the Langkat Regency government to develop the furniture industry. Until now, SME centers have not shown economic development and activity as expected. A prospective strategy to analyze internal and external environmental factors related to development, competitiveness and existence needs to be owned by SME centers. This research aims to analyze internal and external factors, as well as develop alternative strategies for developing the Langkat Furniture SME center. The analysis tools used are the SWOT matrix and QSPM. Previous research did not determine a development strategy for the small industrial sector which focused on centers built by the government with the concept of artificial development. Respondents in this study were SMEs and government employees who knew the conditions of the centers as a whole. The results of the IE matrix analysis show the position of SME centers in quadrant I, namely belonging to the category of growth through vertical integrity. The formulation of alternative strategies from matching each internal and external factor in the SWOT matrix resulted in 9 strategies. The results of the IE and SWOT matrix assessment and analysis of the strategies formulated show that the strategies required regarding the development of SME centers are intensive, namely market penetration, product development and market development. The QSPM analysis displays strategic decisions that are priorities according to the conditions of the Langkat Furniture SME center, namely the commitment of the local government in developing the center.